Radiotherapy treatment modification for prostate cancer patients based on PSMA-PET/CT - Karagiannis Vasileios; Wichmann Viktor; Saarinen Juha; Eigeliene Natalja; Andersen Heidi; Jekunen Antti (BMC, 2025)
Background: Prostate cancer is the most common cancer among men, and its diagnosis and treatment are improving. Our study evaluated how PSMA-PET/CT prior to treatment planning might improve the optimal management of prostate cancer radiotherapy.
Methods: This retrospective pilot study included 43 prostate cancer (PCa) patients referred to our radiation oncologist department, from the urology department, for radiation therapy. 18F-PSMA-PET/CT was ordered by the radiation oncologists mainly due to the lack of resent image staging. The patients were divided into three different groups according to their initially planned treatments: radical radiation therapy (RT) (newly diagnosed PCa patients), salvage RT (patients with biochemical recurrence after radical prostatectomy), or oligometastatic RT (oligometastatic PCa patients with good response after systemic treatment).
Results: Following PSMA-PET/CT, the initially planned RT was changed for 60.5% of the patients due to new findings (metastases and/or recurrent disease). The final treatment choice was effected by PSMA-PET/CT outcome in 60.5% (26/43) of the patients, and in 50% (16/32) of patients, the radiation treatment plan changed following PSMA-PET/CT. Only 39.5% (17/43) of the patients who underwent PSMA-PET/CT were treated according to their initial treatment plans.
Conclusions: Our results indicate that PSMA-PET/CT impacts treatment decisions and the selection of RT as well as adjuvant treatment protocols in the management of prostate cancer.